DEVELOP A STRUCTURED MODEL TO ASSIST THE EVALUATION OF VALUE FOR MONEY ACHIEVED ON PUBLIC PRIVATE PARTNERSHIPS IN LIBYA - Marzok, Mohamed Mahdy; Elhessnawi, Mahmoud Omar (Acta Scientiae et Intellectus, 2024)
Public-private partnerships (PPPs) play an important role in bringing private sector competition to public monopolies in infrastructure development and service provision and in merging the resources of both public and private sectors to better serve the public needs. However, in worldwide practices, there are mixed results, substantial controversy, criticism and conflict over PPPs. The main characteristics of Build-Operate-Transfer “BOT” structure projects are long term contract, Private sector bears a significant share of the risks, and performance based- High level of private investment, it is essential for the public and private partner to extensively evaluate all the potential risks throughout the whole life of the project to decide whether to take up the project or not. This is done through incorporating risk assessment into value for money analysis, which is affected by the amount of risk associated with a project. Therefore, the main objective of this paper is to presents an alternative risk assessment and profit approaches to align benefit both public sector sponsors, by creating value for people, and investor interest, by generating attractive returns in supporting PPP selection.